Microeconomics: principles, problems, and policies - McConnell, Campbell; Brue, Stanley; Flynn, Sean (Boston: McGraw-Hill/Irwin, 2009)
The book builds upon the tradition of leadership by helping the beginning student master the principles essential for understanding the economizing problem, specific economic issues, and the policy alternatives.
Includes Index.
lje 06/09/13
Loans
Keywords: Microeconomics